LEGAL FEMINIST APPROACH TO ABORTION IN TAMIL NADU - A STUDY - P. PAVITHRA (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Induced abortion has been legal in India on a broad range of grounds since the Medical Termination of Pregnancy (MTP) Act was passed in 1971. An estimated 707,900 abortions are performed in Tamil Nadu annually. For 2015, this translates to 33 abortions per 1,000 women of reproductive age Thirty-two per cent of abortions occurring annually in the state an estimated 228,600 are provided in health facilities. More than half (56%) of these are surgical, and the remaining 44% are performed using medical methods of abortion (MMA). Eighty-two per cent of facility-based abortions are provided in private facilities, nearly 17% in public facilities and about 2% in NGO facilities. The majority of abortions in Tamil Nadu (63%) are done using MMA obtained in settings other than health facilities. Five per cent are performed outside of health facilities using other, typically unsafe methods. An estimated 43% of all pregnancies in the state 945,900 in 2015 are unintended. Three-quarters (75%) of these unintended pregnancies end in abortion. Each year in Tamil Nadu, roughly 183,300 women obtain facility-based post abortion care for complications resulting from induced abortion or miscarriage